1991
DOI: 10.1007/bf00370450
|View full text |Cite
|
Sign up to set email alerts
|

Fura-2 imaging of spontaneous and electrically induced oscillations of intracellular free Ca2+ in rat myotubes

Abstract: Rat myotubes have a resting [Ca2+]i of about 82 nM. Myotubes 3-5 days old (quiescent myotubes) display electrically induced and spontaneous transients in the intracellular concentration of free Ca2+ ions ([Ca2+]i) uncoupled to any detectable contraction. By contrast, 1- to 2-day-old myotubes are insensitive to electrical stimuli and, after 6 days in culture, stimulated myotubes always show [Ca2+]i transients and twitch contractions. The spatial distribution of [Ca2+]i variations in quiescent myotubes is hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
19
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
10
19
0
Order By: Relevance
“…In some species, including mouse, the maturation of the E-C coupling mechanism proceeds even in the absence of the nerve (29,39,40). In contrast, in human muscle cells, the nerve plays a critical role in the subcellular distribution and expression of L-type Ca 2ϩ channels and RyRs, in the formation of striated junctions, and in the establishment of the E-C coupling mechanism (14).…”
Section: Discussionmentioning
confidence: 99%
“…In some species, including mouse, the maturation of the E-C coupling mechanism proceeds even in the absence of the nerve (29,39,40). In contrast, in human muscle cells, the nerve plays a critical role in the subcellular distribution and expression of L-type Ca 2ϩ channels and RyRs, in the formation of striated junctions, and in the establishment of the E-C coupling mechanism (14).…”
Section: Discussionmentioning
confidence: 99%
“…(Fong et al, 1990;Grassi et al, 1994;Bakker et al, 1997). The r e s t i n g [Ca2+]i of cultured primary rat myotubes (Grouselle et al, 1991;Cognard et al, 1993;Jaimovich and Rojas, 1994) is higher than that of L 6 muscle cells, which is independent of the composition of the differentiation medium. The responses of [Ca2+]i on addition of acetylcholine, a high concentration of KC1, or caffeine to the perfusion fluid establish the presence of a functional excitation-contraction coupling in C2C12 myotubes (Grassi et al, 1994), as has been observed in cultured mouse and human muscle ceils (Benders et al, 1997a(Benders et al, , 1997bSteeghs et al, 1997).…”
Section: Hs Ubementioning
confidence: 94%
“…On the other hand, skeletal muscle cells develop excitability and contractile properties during the first stages of myogenesis. This phenotype has been associated to the onset of voltage-dependent channel protein expression (sodium and calcium channels) and to the maturation of the excitation-contraction apparatus (7)(8)(9). At more advanced developmental stages, muscle activity is controlled by motor innervation (10).…”
mentioning
confidence: 99%